2011
DOI: 10.1158/1078-0432.ccr-10-3394
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Promoter CpG Island Hypermethylation in Cancer: Location, Location, Location!

Abstract: The genetic and epigenetic alterations that underlie cancer pathogenesis are rapidly being identified. This provides novel insights in tumor biology as well as in potential cancer biomarkers. The somatic mutations in cancer genes that have been implemented in clinical practice are well defined and very specific. For epigenetic alterations, and more specifically aberrant methylation of promoter CpG islands, evidence is emerging that these markers could be used for the early detection of cancer as well as predic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
102
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 124 publications
(104 citation statements)
references
References 77 publications
(69 reference statements)
2
102
0
Order By: Relevance
“…CpG methylation can be analysed after nucleic acid isolation from various cellular and cell-free sources. 7 Several techniques to analyse CpG methylation have been developed, encompassing locus-specific methods that interrogate single to few genes as well as genome-wide and whole genome methods capturing the epigenomic landscape in a high-throughput manner. For biomarker discovery studies, mostly genome-wide methods are applied as these enable comparisons of large parts of the DNA-methylome between different sample groups.…”
mentioning
confidence: 99%
“…CpG methylation can be analysed after nucleic acid isolation from various cellular and cell-free sources. 7 Several techniques to analyse CpG methylation have been developed, encompassing locus-specific methods that interrogate single to few genes as well as genome-wide and whole genome methods capturing the epigenomic landscape in a high-throughput manner. For biomarker discovery studies, mostly genome-wide methods are applied as these enable comparisons of large parts of the DNA-methylome between different sample groups.…”
mentioning
confidence: 99%
“…Recent analyses of the spatial distribution of differentially methylated CpG sites have brought into question the relevance of previously reported methylation studies (Portela & Esteller 2010, van Vlodrop et al 2011. Unbiased global methylation analyses using immunocapturing techniques demonstrated that aberrantly methylated regions in colon cancer cells were not restricted to CpG islands (Weber et al 2005).…”
Section: Recent Issues In Dna Methylationmentioning
confidence: 99%
“…It is worth noting that C-DMRs displaying hypermethylation in cancer tend to associate with regions close to CpG islands (54% are situated within 500 bp of a CpG island) whereas those showing hypomethylation rarely associate closely with CpG R52 M Cusack and P Scotting islands (Irizarry et al 2009). Evidence that epigenetic silencing can occur over long distances (Frigola et al 2006, Tiwari et al 2008 and that gene silencing can depend on the methylation of specific sites within CpG islands (Zinn et al 2007, Sohn et al 2010 indicates that analysis of only a few CpG sites in a gene promoter region is likely to be insufficient to accurately reflect the methylation status of that gene (van Vlodrop et al 2011).…”
Section: Recent Issues In Dna Methylationmentioning
confidence: 99%
See 2 more Smart Citations